Influence of Biomass Ash on the Performance and Durability of Mortar - Ramdane, Rihab; Kherraf, Leila; Abdelouahed, Assia; Belachia, Mouloud (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This work revolves around the study of the partial substitution of cement by biomass ash (residue generated during incineration of wood waste) in mortar. The introduction of wood ash in the cement formulation allows solving some problems related to the lack of construction materials and protecting the environment. To carry out this work we have introduced wood ash as an addition which partially substitutes cement at three different replacement percentages (5%, 10% and 15%).
Keywords: cement; substitution; biomass; additions; performance; durability of mortar; zamiennik; biomasa; dodatki; trwałość zapraw